Port cities and global legacies : urban identity, waterfront work, and radicalism - Mah, Alice; SpringerLink (Online service). (London : Palgrave Macmillan UK, 2014)
Port cities have distinctive global dynamics, with long histories of casual labour, large migrant communities, and international trade networks. This in-depth comparative study examines contradictory global legacies across themes of urban identity, waterfront work and radicalism in key post-industrial port cities worldwide.
Keywords: Social sciences; Urban geography; Environmental management; Sociology, Urban; Human geography